2017
DOI: 10.25275/apjabssv3i2bus1
|View full text |Cite
|
Sign up to set email alerts
|

The Immediate Impact of Instagram Posts on Changing the Viewers’ Perceptions Towards Travel Destinations

Abstract: This study aims to measure the immediate impact of User-Generated-Contents (UGC) in forms of Instagram images on changing the viewer's perceptions towards a travel destination.By using an experimental design and subsequent t-Test in SPSS, the viewers' perceptions of a destination (Lebanon) pre-and post-exposure to selected Instagram images were investigated.The findings show that Instagram posts were effective in changing the viewers' perceptions and it can influence viewers' ` behavioural intentions during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 21 publications
2
22
0
2
Order By: Relevance
“…This practice is particularly representative in the case of Algarve, and our results have demonstrated that photos posted by tourists provide an effective resource for building and promoting a destination's image. This form of tourism promotion by DMOs in social media was identified, but they only focused on content generated by travel bloggers [4]. However, their results revealed the particular contribution of microbloggers to their promotion campaign.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This practice is particularly representative in the case of Algarve, and our results have demonstrated that photos posted by tourists provide an effective resource for building and promoting a destination's image. This form of tourism promotion by DMOs in social media was identified, but they only focused on content generated by travel bloggers [4]. However, their results revealed the particular contribution of microbloggers to their promotion campaign.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, social media should be considered not only as a communication tool, but also as an active component in the destination's image [1,4,14]. As Hanan and Putit [18] expressed, "Snapping a picture can create the certain kind of emotion and feeling toward the destination.…”
Section: Destination Image and Instagrammentioning
confidence: 99%
See 3 more Smart Citations